Estimating the size of underground economy in Indonesia - Wibowo, Sasmito H.; Sharma, Subhash C. (2005)
The size of the underground economy in Indonesia is estimated from 1976 to 1999 by using the currency demand model. We observe that during these years, on average the underground economy is about a quarter of the reported GDP. We further note that during transitions, whether transition in tax law, economy, or in politics, the size of the underground economy changes significantly. During normal time, the size tend to be lower than the average. Specifically, during the major overhaul of Indonesia's tax law in 1986 and in 1998's recession the size of the unreported economic activities increased significantly. - Reproduced.
Keywords: Informal sector - Indonesia; Informal sector